The comparative cost-effectiveness of colorectal cancer screening using faecal immunochemical test vs. colonoscopy - Wong, Martin CS; Ching, Jessica YL; Chan, Victor CW; Sung, Joseph JY (Scientific reports, 2015)
Faecal immunochemical tests (FITs) and colonoscopy are two common screening tools for colorectal cancer(CRC). Most cost-effectiveness studies focused on survival as the outcome and were based on modeling techniques instead of real world observational data. This study evaluated the cost-effectiveness of these two tests to detect colorectal neoplastic lesions based on data from a 5-year community screening service. The incremental cost-effectiveness ratio (ICER) was assessed based on the detection rates of neoplastic lesions and costs including screening compliance, polypectomy, colonoscopy complications and staging of CRC detected. A total of 5,863 patients received yearly FIT and 4,869 received colonoscopy. Compared with FIT, colonoscopy detected notably more adenomas (23.6% vs. 1.6%) and advanced lesions or cancer (4.2% vs. 1.2%). Using FIT as control, the ICER of screening colonoscopy in detecting adenoma, advanced adenoma, CRC and a composite endpoint of either advanced adenoma or stage I CRC was US$3,489, US$27,962, US$922,762 and US$23,981 respectively. The respective ICER was US$3,597, US$439,513, -US$2,765,876 and US$32,297 among lower-risk subjects; whilst the corresponding figure was US$3,153, US$14,852, US$184,162 and US$13,919 among higher-risk subjects. When compared to FIT, colonoscopy is considered cost-effective for screening adenoma, advanced neoplasia and a composite endpoint of advanced neoplasia or stage I CRC.